Soils and fire jointly determine vegetation structure in an African savanna. Issue 4 (25th August 2017) - Staver, A. Carla; Botha, Judith; Hedin, Lars
Summary: Savanna vegetation is variable, and predicting how water, nutrients, and chronic disturbances interact to determine vegetation structure in savannas represents a challenge. Here, we examined in situ interactions among rainfall, soils, grasses, fire, and elephants that determine tree layer responses to resource gradients in Kruger National Park in South Africa, using 363 long‐term monitoring sites throughout the park. Grass biomass increased with rainfall and on nutrient‐rich clay soils. Fire frequency, too, increased with rainfall. Conversely, tree density was greater on sandier soils, where water infiltrates more readily, and in areas where the maximum interval between fires was longer, irrespective of average fire frequency. Elephant density responded positively to tree density, but did not contribute significantly to decreasing tree density. Savanna vegetation structure was reasonably predictable, via a combination of rainfall (favoring grasses), soil (sandy soils favoring trees), and fire (limiting trees until a longer interval between fires allows them to establish). Explicit consideration of bottom‐up and top‐down interactions may thus contribute to a predictive understanding of savanna vegetation heterogeneity.